Contribution of tractography to neuroanatomical terminology - short association tracts of the frontal lobe - Slobodan Malobabić; Goran Spasojević (Биомедицинска истраживања, 2024)
Enormous development of neuroimaging technologies, and subsequently of research methods, opened new era of in vivo research of the white matter anatomy. This Reviews analyzes recent connectomics and imaging data about short association fibers of the frontal lobe, and relates it to current status and to further development of anatomical terminology. In some recent terminologies, such as in Neuroanatomical Terminology, or in Terminology of German Anatomical Society, under the section Fibrae associationis lobares Fasciculus frontalis obliquus, Fasciculus frontalis orbitopolaris and Fasciculus frontomarginalis have been listed. Also, in this Reviews anatomy of the potential candidates for adding into new terminologies is described, such as Fronto-parietal U-tracts, Fronto-insular tracts, and Frontal longitudinal fasciculus system. Suggestions considered in this Reviews are related to our research of human brain morphology in order to overcome the lack of postmortem brain specimens, to contribute to the linking of different data, and to enable better morphological correlations.
Keywords: frontal lobe; association fibers; tractography; terminology; white matter